The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5696/2156-9614-9.23.190903
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Solid Waste Disposal Operational Performance in Wa Municipality, Ghana

Abstract: Background. The generation and management of solid waste pose potential adverse impacts on human health and the environment. Objective. The present study examines the operational performance of municipal solid waste (MSW) disposal in the Wa Municipality, Ghana. Methods. The study applied both qualitative and quantitative research methods and modelled the Wa Municipality's MSW disposal system using the municipal solid waste decision support to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The study recommended mechanical biological treatment (MBT) primarily because it can separate the organic component of MSW from the inorganic component with the possibility of obtaining non-biodegradable resources for other purposes. Using the MSW decision support tool, Brown et al [20] assessed the performance of municipal solid waste disposal operations in one of Ghana's municipalities, Wa. The study recommended an integrated system consisting of separation, composting, incineration and RDF to landfill disposal within the municipality since it had a lesser impact on health.…”
Section: Introductionmentioning
confidence: 99%
“…The study recommended mechanical biological treatment (MBT) primarily because it can separate the organic component of MSW from the inorganic component with the possibility of obtaining non-biodegradable resources for other purposes. Using the MSW decision support tool, Brown et al [20] assessed the performance of municipal solid waste disposal operations in one of Ghana's municipalities, Wa. The study recommended an integrated system consisting of separation, composting, incineration and RDF to landfill disposal within the municipality since it had a lesser impact on health.…”
Section: Introductionmentioning
confidence: 99%
“…Studies proved that the lack of access to waste collection services, inadequate bins [40][41], nonoperation of disposal facilities [9], and insufficient technical capacity to handle and dispose of wastes by SWM personnel [41] encourage improper waste practices among waste generators. Maintaining the quality, frequency, and regularity of waste collection [42] and widening the collection coverage by including the remote places in the provision [43] are needed to achieve good solid waste management at the community level.…”
Section: 2) Comprehensive Solid Waste Management (Cswm)mentioning
confidence: 99%
“…Sumalde [45] found that implementing SWM is very costly for LGUs. Lack of financial resources affects the municipality's ability to manage waste effectively [41,46]. The LGUs need the financial support they require for the complete and satisfying delivery of the service of the government in their action toward SWM [6].…”
Section: 4) Financing Solid Waste Management (Fswm)mentioning
confidence: 99%
“…The key objectives of sustainable MSWM are to constantly improve the urban living environment, increase economic productivity, advance direct public health benefits, and facilitate safe, dignified and secure employment opportunities [8]. An integrated MSWM system consists of the key processes from the point of waste generation to final waste disposal including: 1. waste identification, 2. handling the waste at source, 3. separation and storage at the source, 4. collection from the source of generation, and 5. transfer or transport for final process of disposal/recycle/recovery [9,10].…”
Section: Introductionmentioning
confidence: 99%